Estudio de factibilidad para la creación de un centro de acopio para la asociación de productores de ciclo corto (Aprocico) - Fuentes Triviño, Maria Fernanda (2013)
This project has to conduct a feasibility study for the acquisition of a storage facility and marketing of agricultural products that will benefit members and countless APROCICO farmers Quevedo area. This project will be subject to the development of this marketing strategy and economic environment of the county. Similarly, it will be subject to economic evaluation of marketing, marketing, investment and technological aspect to the acquisition of the collection center, announcing the purchase means that upon completion of the process will serve marketing, selection, drying, transport and stored trade short cycle production (corn, soybeans, rice, etc.) The purpose of this project is to promote and create an environment for agricultural development. APROCICO plus policies delineate the productive sector for the benefit of farmers Quevedo area and surrounding areas, to supplement their benefits to small and medium farmers, acquiring Silos Plant Collection and milled grain, favoring a policy of protecting the interests of small and medium farmer, by buying their crops of corn, soybeans and rice winter and summer, appreciations fair in the amount or purchase of products, prices set between the producers, the Ministry of Agriculture, and managed by agricultural unions such as APROCICO. Keywords: APROCICO, collection center, investment, farmers.